2004
DOI: 10.1152/japplphysiol.00964.2003
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exercise to fatigue in humans impairs skeletal muscle Na+-K+-ATPase activity, sarcoplasmic reticulum Ca2+release, and Ca2+uptake

Abstract: Prolonged exhaustive submaximal exercise in humans induces marked metabolic changes, but little is known about effects on muscle Na+-K+-ATPase activity and sarcoplasmic reticulum Ca2+ regulation. We therefore investigated whether these processes were impaired during cycling exercise at 74.3 +/- 1.2% maximal O2 uptake (mean +/- SE) continued until fatigue in eight healthy subjects (maximal O2 uptake of 3.93 +/- 0.69 l/min). A vastus lateralis muscle biopsy was taken at rest, at 10 and 45 min of exercise, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 60 publications
9
66
0
5
Order By: Relevance
“…A number of studies have reported that Ca 2ϩ release from isolated SR is reduced by ϳ20 -40% following prolonged or intense exercise in humans (210,284,285) and rodents (161), although some studies found no change (111,396) or a reduction in slow-twitch but not fast-twitch muscle (161,221). It is unclear how long this effect persists after exercise, as this was only examined in one study to date, and the results were somewhat equivocal at the one recovery time examined (3.5 h) (210 ] i also greatly prolongs PCD in Xenopus fast-twitch fibers (69,70,269).…”
Section: Prolonged Reduction In Ca 2؉ Releasementioning
confidence: 99%
“…A number of studies have reported that Ca 2ϩ release from isolated SR is reduced by ϳ20 -40% following prolonged or intense exercise in humans (210,284,285) and rodents (161), although some studies found no change (111,396) or a reduction in slow-twitch but not fast-twitch muscle (161,221). It is unclear how long this effect persists after exercise, as this was only examined in one study to date, and the results were somewhat equivocal at the one recovery time examined (3.5 h) (210 ] i also greatly prolongs PCD in Xenopus fast-twitch fibers (69,70,269).…”
Section: Prolonged Reduction In Ca 2؉ Releasementioning
confidence: 99%
“…Muscle fatigue is a very complex phenomenon that involves multiple cellular correlates, e.g., transmission failure of action potentials, tubular excitation spread failure, voltage sensor dysregulation, SR Ca 2ϩ release, metabolic impairment through ATP depletion or reuptake alterations, or myofibrillar protein alterations (13,28,172,417,572,657). In critically ill patients, muscle fatigue is usually only assessed via nerval routes either using voluntary muscle exercise (278) or nerve stimulation (181).…”
Section: E Muscle Fatigue In Critical Illnessmentioning
confidence: 99%
“…Finally, and perhaps of greatest importance, the Ca 2ϩ release channel is also strongly inhibited by cytoplasmic Mg 2ϩ (80) (37), although it is apparent that they are not the only metabolic factors involved in reducing Ca 2ϩ release in fatigue (38). A number of studies have reported that Ca 2ϩ release from isolated SR is reduced up to ϳ40% following prolonged or intense exercise in humans (63,83,84). However, in such studies the Ca 2ϩ release was triggered by non-physiological means, such as by caffeine, chloro-m-cresol, or the oxidizing agent Ag ϩ , and the rate of release was more than 30 times slower than occurs when activating Ca 2ϩ release by the normal voltage sensor mechanism.…”
Section: Modification Of Sr Calcium Releasementioning
confidence: 99%